Theoretical and Methodological Aspects of Tacit Knowledge Research of Educators at Youth Educational Centres in Poland in the Context of Social Worlds Theory - Gabriela Dobińska (Nicolaus Copernicus University in Toruń, 2020)
The aim of the article is to present theoretical and methodological reflections on research on the tacit knowledge and the social world of educators at młodzieżowe ośrodki wychowawcze [youth educational centres]. The introduction to the article contains a review of literature and an analysis of superior analytical categories in the context of social rehabilitation. Next, a methodological framework and preliminary assumptions regarding the test procedure are presented. The research project discussed in this paper is formed as an ethnography, the course of which is indicated by analytical procedures of the grounded theory methodology. The empirical material consists of a 12-month observation of everyday work of educators at youth educational centres and 17 interviews conducted with the educators at youth educational centres from Poland. The critical analysis of studies presents the challenges, potentials and values, as well as the difficulties resulting from limitations of the methodological assumptions. Three areas were analysed: negotiating the conditions for conducting research, defining the role of the researcher and the method of recruiting interviewees.